Dual-site phosphorylation of the control of virulence regulator impacts group a streptococcal global gene expression and pathogenesis. - Nicola Horstmann; Miguel Saldaña; Pranoti Sahasrabhojane; Hui Yao; Xiaoping Su; Erika Thompson; Antonius Koller; Samuel A Shelburne (PLoS Pathogens)
Phosphorylation relays are a major mechanism by which bacteria alter transcription in response to environmental signals, but understanding of the functional consequences of bacterial response regulator phosphorylation is limited. We sought to characterize how phosphorylation of the control of virulence regulator (CovR) protein from the major human pathogen group A Streptococcus (GAS) influences GAS global gene expression and pathogenesis. CovR mainly serves to repress GAS virulence factor-encoding genes and has been shown to homodimerize following phosphorylation on aspartate-53 (D53) in vitro. We discovered that CovR is phosphorylated in vivo and that such phosphorylation is partially heat-stable, suggesting additional phosphorylation at non-aspartate residues. Using mass spectroscopy along with targeted mutagenesis, we identified threonine-65 (T65) as an additional CovR phosphorylation site under control of the serine/threonine kinase (Stk). Phosphorylation on T65, as mimicked by the recombinant CovR T65E variant, abolished in vitro CovR D53 phosphorylation. Similarly, isoallelic GAS strains that were either unable to be phosphorylated at D53 (CovR-D53A) or had functional constitutive phosphorylation at T65 (CovR-T65E) had essentially an identical gene repression profile to each other and to a CovR-inactivated strain. However, the CovR-D53A and CovR-T65E isoallelic strains retained the ability to positively influence gene expression that was abolished in the CovR-inactivated strain. Consistent with these observations, the CovR-D53A and CovR-T65E strains were hypervirulent compared to the CovR-inactivated strain in a mouse model of invasive GAS disease. Surprisingly, an isoalleic strain unable to be phosphorylated at CovR T65 (CovR-T65A) was hypervirulent compared to the wild-type strain, as auto-regulation of covR gene expression resulted in lower covR gene transcript and CovR protein levels in the CovR-T65A strain. Taken together, these data establish that CovR is phosphorylated in vivo and elucidate how the complex interplay between CovR D53 activating phosphorylation, T65 inhibiting phosphorylation, and auto-regulation impacts streptococcal host-pathogen interaction.